Factors predicting the long-term renal function in boys presenting with posterior urethral valves at Tygerberg Children's Hospital, South Africa : a ten year study - De Wet, Matthys Johannes (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMed)--Stellenbosch University, 2014.